Pyruvate enolate arylation and alkylation: OBO ester protected pyruvates as useful reagents in organic synthesis - Alves Esteves, C; Hall, C; Smith, P; Donohoe, T (American Chemical Society, 2017)
A protected pyruvate equivalent is described that allows arylation and arylation/alkylation reactions to be performed at the methyl group. Utilization of the OBO derivative of the pyruvate ester allowed the application of palladium catalyzed arylation reactions together with subsequent alkylation, under basic conditions. Moreover, the OBO protecting group could be easily removed in one step to provide access to a wide range of substituted pyruvate derivatives.